Analysis of Financial Performance Based on Activity Ratio and Profitability Ratio in Food and Beverage Industry Companies Listed on The Indonesia Stock Exchange (IDX) Period 2016–2020 - Sahib, Muhammad Khaedar; Rustam, Andi; Fitrah, Fitrah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the Financial Performance of Food and Beverage Industry Companies listed on the Indonesia Stock Exchange from 2016 to 2020. The type of research used in this research is Quantitative Descriptive. types of data using secondary data obtained from financial report data. the sample in this study is 5 companies taken based on certain criteria, namely the Purposive Sampling technique . Based on the results of calculations from the analysis that has been carried out on the financial statements that have been obtained from food and beverage sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period using financial ratios, namely activity and profitability, it can be concluded that the average value of the ratio Of the 8 food and beverage sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period, the company's condition was not good, as can be seen from the Activity Ratio Analysis as measured using Total Asset Turnover and investment turnover , it shows that Food and Beverage Industry Companies can be categorized as in a which is not good because it is still below industry standards meaning that the company industry food And drink Not yet Enough stable And efficient in its activity cycle to obtain income while Profitability Ratio Analysis as measured using Net profit Margin, Return On Assets and Return On Investment shows that food and beverage companies can be categorized as in unfavorable condition because the value generated is still below the industry standard. means that the company is still not able to obtain profits or gains from sales or from capital alone